Performance analysis of the Takoradi thermal power plant - Seckley, Emmanuel Mawuli (2011)
A Thesis presented to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for a Master of Science Degree in Mechanical Engineering.